A multi-physics approach for modelling noise mitigation using an air-bubble curtain in impact pile driving - Peng, Yaxi; Jarquin Laguna, Antonio; Tsouvalas, Apostolos (Frontiers in Marine Science, 2023)
Underwater noise from offshore pile driving has raised significant concerns over its ecological impact on marine life. To protect the marine environment and maintain the sustainable development of wind energy, strict governmental regulations are imposed. Assessment and mitigation of underwater noise are usually required to ensure that sound levels stay within the noise thresholds. The air-bubble curtain system is one of the most widely applied noise mitigation techniques. This paper presents a multi-physics approach for modeling an air-bubble curtain system in application to offshore pile driving. The complete model consists of four modules: (i) a compressible flow model to account for the transport of compressed air from the offshore vessel to the perforated hose located in the seabed; (ii) a hydrodynamic model for capturing the characteristics of bubble clouds in varying development phases through depth; (iii) an acoustic model for predicting the sound insertion loss of the air-bubble curtain; and (iv) a vibroacoustic model for the prediction of underwater noise from pile driving which is coupled to the acoustic model in (iii) through a boundary integral formulation. The waterborne and soilborne noise transmission paths are examined separately, allowing us to explore the amount of energy channeled through the seabed and through the bubble curtain in the water column. A parametric study is performed to examine the optimal configuration of the double bubble curtain system for various soil conditions and pile configurations. Model predictions are compared with measured data. The model allows for a large number of simulations to examine different configurations of a single bubble curtain and a double big bubble curtain.